Edition Explosionalismus - Čapková, Eva (Bohemica Olomucensia, 2016)
Edition Explosionalism is one of the early Samizdat editions that were published in the 50s of the last century. It was founded by the graphic artist Vladimir Boudník, who was also the main author and editor of the published texts. The edition was short-lived and was only published for around a year. In the early 70s, it was revived by Boudníks student Oldřich Hamera. However, he was working under completely different surrounding conditions and was also supported by Bohumil Hrabal. Contributions to this later edition, either financially or with own works, mainly came from Hameras circle of friends.
Keywords: Edition Explosionalismus; Protosamizdat; Samizdat; Vladimír Boudník; Oldřich Hamera; Bohumil Hrabal